2001
DOI: 10.1152/jappl.2001.90.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of physical training in ovariectomized and hyperestrogenic rats

Abstract: This study was undertaken to evaluate the effects of regular endurance-type exercise on glucose tolerance and glucose-stimulated insulin response (GSIR) in ovariectomized (OVX) rats with and without estrogen replacement. To do that, OVX Sprague-Dawley rats were compared with an OVX estradiol-treated group (OVXE2) and a sham-operated (Sham) group. Each of these groups was subdivided into a sedentary and a treadmill-trained (8 wk) group. Intravenous glucose tolerance tests (0.5 g/kg) were conducted in all rats 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
3
7

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 24 publications
7
40
3
7
Order By: Relevance
“…24,25 We recently reported that exercise training in OVX rats results in an improvement of the insulin-resistant condition without any reduction in body weight. 7 From the present data, it may be suggested that a reduction in body fat contributes to the exercise training-induced improvement in insulin sensitivity in OVX rats.…”
Section: Body Composition In Ovariectomized Trained Ratsmentioning
confidence: 55%
See 4 more Smart Citations
“…24,25 We recently reported that exercise training in OVX rats results in an improvement of the insulin-resistant condition without any reduction in body weight. 7 From the present data, it may be suggested that a reduction in body fat contributes to the exercise training-induced improvement in insulin sensitivity in OVX rats.…”
Section: Body Composition In Ovariectomized Trained Ratsmentioning
confidence: 55%
“…7 OVX resulted in a significant (P < 0.01) reduction of 17b-estradiol levels (Table 1). However, 17b-estradiol levels in OVX rats were still approximately 75% of those measured in Sham.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations